Material deprivation items in SHARE Wave 5 data: a contribution to a better understanding of differences in material conditions in later life - Maja Adena; Michal Myck; Monika Oczkowska (Ageing in Europe - Supporting Policies for an Inclusive Society, 2015)
* New material deprivation items (MDIs) improve the understanding of individual economic situation in later life * MDIs have advantages over simple subjective measures of material conditions and can prove useful in analysis of the effect of economic circumstances on well-being * MDIs may prove valuable when constructing complex measures of material conditions and multidimensional measures of exclusion
Keywords: 300